PENERAPAN MODEL PENYEMBUHAN DENGAN REGRESI COX HAZARD PROPORSIONAL PADA PENYAKIT KANKER KOLOREKTAL - Wirna Arifitriana; Danardono Danardono (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
Survival  analysis  is  a  statistical  technique  used  to  analyze  the  data,  aims  to determine the variables that affect the outcome of a beginning to end the incident. One model of survival is a cure model is useful for estimating the proportion of patients who recover and the probability of survival of patients who did not recover until   the   deadline   given.   Analysis   on   Cox   regression   cure   model   Hazard Proportional with Maximum Likelihood Estimates and Algorithm Expectation Maximization (EM). Keywords: Cox Proportional Hazard Cure Model, MLE, EM algorithm, likelihood ratio test, Wald test.